KONVERGENSI PENDAPATAN DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA DI PULAU JAWA DAN BALI TAHUN 2006-2013 - B01111032, GLORIA RISKA (Jurnal Pembangunan dan Pemerataan, 2015)
Convergence is a condition that describes the narrowing of the gap ordisparity of a variable between regions within a certain period. This researchaimed to analyze if the income convergence (Ïƒ-convergence) in Java and Baliexisted or not and to analyze the factors that influence the convergence in Javaand Bali (Î²- convergence). This research used secondary data from GrossRegional Domestic Product (GRDP) per capita in 2006-2013, investment in 2006-2013 and number of workers employed in 2006-2013 in Java and Bali which wereobtained from the Central Statistics Agency (BPS).The analysis used in this research was the analysis of sigma convergenceby calculating the coefficient of variation, and beta convergence analysis whichwas divided into absolute convergence and conditional convergence. The resultsindicated that the analysis of sigma convergence experienced two dispersion ofsigma convergence in Java and Bali, the first in 2006-2012 seen from the resultsof coefficient of variation which decline each year. Meanwhile, in 2012-2013there was no convergence sigma indicated by the results of the coefficient ofvariation increased.Results of the absolute convergence analysis showed that absoluteconvergence occurs in Java and Bali. The Results of the conditional convergenceanalysis showed that there was conditional convergence by using the factors thatinfluenced income convergence In Java and Bali Year 2006-2013, i.e early GRDP per capita, Investment and Labor showed a significant influence.Keywords : Convergence, Gross Domestic Product, investment, laborabsorbed, Ïƒ-convergence, Î²-convergence, absolute convergenceand conditional convergence.